2009
DOI: 10.1001/jama.2009.1201
|View full text |Cite
|
Sign up to set email alerts
|

Postlicensure Safety Surveillance for Quadrivalent Human Papillomavirus Recombinant Vaccine

Abstract: N JUNE 8, 2006, THE FOOD and Drug Administration (FDA) licensed the quadrivalent human papillomavirus recombinant vaccine (qHPV) (Gardasil; Merck & Co, Inc, Whitehouse Station, New Jersey) for females aged 9 to 26 years to prevent infection with genital human papillomavirus (HPV) types 6, 11, 16, and 18. 1 Later that month, the Advisory Committee on Immunization Practices (ACIP) recommended routine vaccination of females aged 11 to 12 years with 3 doses of qHPV and catch-up vaccination for females aged 13 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
184
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(198 citation statements)
references
References 23 publications
6
184
2
6
Order By: Relevance
“…A number of cases of possibly immune-based inflammatory neurodegenerative disorders involving the central nervous system, known as acute disseminated encephalomyelitis, following Gardasil ® injections have been reported in world literature [12][13][14][15][16][17][18]. Among 12,424 reported adverse events following Gardasil ® vaccination from June 1, 2006 through December 31, 2008, there were 32 deaths with a mean age of 18 years old, who died 2 to 405 days after the last Gardasil ® injection [19]. Medical records and autopsy reports on 20 of the 32 deaths were available for review and confirmed there were 4 unexplained deaths and 6 cardiac-related deaths [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of cases of possibly immune-based inflammatory neurodegenerative disorders involving the central nervous system, known as acute disseminated encephalomyelitis, following Gardasil ® injections have been reported in world literature [12][13][14][15][16][17][18]. Among 12,424 reported adverse events following Gardasil ® vaccination from June 1, 2006 through December 31, 2008, there were 32 deaths with a mean age of 18 years old, who died 2 to 405 days after the last Gardasil ® injection [19]. Medical records and autopsy reports on 20 of the 32 deaths were available for review and confirmed there were 4 unexplained deaths and 6 cardiac-related deaths [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among 12,424 reported adverse events following Gardasil ® vaccination from June 1, 2006 through December 31, 2008, there were 32 deaths with a mean age of 18 years old, who died 2 to 405 days after the last Gardasil ® injection [19]. Medical records and autopsy reports on 20 of the 32 deaths were available for review and confirmed there were 4 unexplained deaths and 6 cardiac-related deaths [19]. No investigative work was attempted to confirm or to exclude any link of a death to Gardasil ® vaccination although there was disproportional reporting of syncope among the Gardasil ® recipients [19].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Differences between HPV infection and other vaccine preventable diseases may contribute to resistance to school requirements. 9 HPV vaccines are primarily intended to prevent a genital cancer caused by a sexually transmitted virus.…”
mentioning
confidence: 99%
“…One with quadrivalent human papilloma virus vaccine (Gardasil Ò ) 23 in which no additional clinical data were given and 2 24,25 with 23 valent pneumococcal polysaccharide vaccine (Pneumovax Ò ). The latter cases reported in females 59 and 76 years old respectively were diagnosed as pseudoseptic arthritis of the glenohumeral joint.…”
Section: Intra-articular Injectionmentioning
confidence: 99%